Врожайність посівів ячменю ярого залежно від застосування інсектицидів в Степу України - Хлевицький, Роман Вікторович; Khlevytskyi, Roman (ЦНТУ, 2023)
Головна мета досліджень полягагала у визначеннні ефективності новітніх інсектицидів для обмеження чисельності та шкодочинності шкідників у посівах ячменю ярого. Для боротьби з шкідниками у посівах ярого ячменю рекомендовано інсектицид Фосорган Доу у нормі 1,0 л/га та Кононір Доу у нормі 0,06 кг/га. Застосування цих інсектицидів при вирощуванні ячменю ярого забезпечує істотне зростання врожайності та високі показники економічної ефективності. The main goal of the research was to determine the effectiveness of the latest insecticides for limiting the number and harmfulness of pests in spring barley crops. For pest control in spring barley crops, the insecticide Phosorgan Dow at the rate of 1.0 l/ha and Kononir Dow at the rate of 0.06 kg/ha is recommended. The use of these insecticides during the cultivation of spring barley provides a significant increase in yield and high indicators of economic efficiency.
The yield of spring barley crops depending on the use of insecticides in the Steppe of Ukraine
Keywords: ячмінь ярий; шкідники; врожайність; spring barley; pests; productivity